ANALYSIS & SOLUTION OF THE PROBLEMS FACED BY THE FRESH IPE GRADUATES AT THEIR INITIAL CAREER: A CASE STUDY - Rahman, Md. Asfakur; Islam, Md. Tasminul (Social work and education, 2018)
Department of Industrial & Production Engineering started its glorious journey from 2006 in Rajshahi University of Engineering & Technology. Since then approximately 250 students graduated and continuously enhancing the global quality of the department through leading discovery and innovation. Despite their shines in career, some problems come their way and make them realize that they should be more careful about them in their University life. In order to get the regarding information, we surveyed about 100 graduates of IPE from different series. They are now working in different sectors with a different designation. Their experience about their career life will help us to find out the problems faced by the fresh IPE graduates as well as it will help us to solve the problems in our University life. We analyzed the data & build methodology through the brainstorming process & finally achieved our result. This will provide a way to overcome the problems faced by the fresh IPE graduates in their initial career.